Positioning control of Pneumatic Artificial Muscle Systems using improved nominal characteristic trajectory following control - Tang, Teng Fong (2019)
Pneumatic Artificial Muscle (PAM) is a new type of pneumatic actuator that duplicates the behaviour of skeletal muscle, where it contracts to generate a pulling force via pressurised air and retracts passively when air is depressurised. The PAM has the characteristics that meet the need of robotic applications, such as lightweight, high power-to-weight ratio performance, and safe in use characteristic. However, the PAM exhibits strong nonlinear characteristics which are difficult to be modelled precisely, and these characteristics have led to low controllability and difficult to achieve high precision control performance. This research aims to propose and clarify a practical controller design method for motion control of a pneumatic muscle actuated system. A nominal characteristic trajectory following (NCTF) control is proposed, and this controller emphasises simple design procedure, which it is designed without the exact model parameters, and yet is able to demonstrate high performance in both point-to-point and continuous motions. The NCTF control is composed of a nominal characteristic trajectory (NCT) and a PI compensator. The NCT is the reference motion trajectory of the control system, and the PI compensator makes the mechanism motion follows the constructed NCT. The NCT is constructed on a phase plane using the deceleration motion of the mechanism in open-loop positioning condition. However, the conventional NCTF control does not offer a promising positioning performance with the PAM mechanism, where it exhibits large vibration in the steady-state before the mechanism stopping and tends to reduce the motion accuracy. Therefore, the main goal of this study is to improve the conventional NCTF control for high positioning control of the PAM mechanism. The conventional NCTF control is enhanced by removing the actual velocity feedback to eliminate the vibration problem, added an acceleration feedback compensator to the plant model and a reference rate feedforward to solve the low damping characteristic of the PAM mechanism in order to improve the tracking following characteristic. The design procedure of the improved NCTF control remains easy and straightforward. The effectiveness of the proposed controller is verified experimentally and compared with the conventional NCTF and classical PI controls in positioning and tracking motion performances. The experimental results proved that the improved NCTF control reduced the positioning error up to 90% and 63% as benchmarked to the PI and conventional NCTF controls respectively, while it reduced up to 92% (PI) and 95% (NCTF) in the tracking error. In the robustness evaluation, the comparative experimental results demonstrated that the improved NCTF control has higher robust against the irregular signals than the PI and the conventional NCTF controls. This can be concluded that, the improved NCTF control has demonstrated high positioning accuracy and fast tracking performance at different working range and frequencies as well as high robustness against the irregular signals. Overall, the improved NCTF control has showed the capability in performing high precision motion and offered promising results for the PAM mechanism.